Evaluating the Structure of Prenatal Care Using the Donabedian Model: A Study at Health Centers in Gorgan, Iran - Parvin Vizvari; Fatemeh Dabbaghi; Ghareman Mamoodi; Akram Sanagoo (Golestan University Of Medical Sciences, 2018)
Introduction: Healthcare centers aim to improve the quality of managed care using a diverse range of organizational strategies and through management of patients' health and behavior. The goal of prenatal care is to ensure the health of future mothers during the prenatal and postnatal periods. The purpose of this study was to evaluate the structure of prenatal care in health centers of Gorgan (Iran) based on the Donabedian model. Materials and methods: This descriptive-analytical study was carried out in 18 of 22 health centers in Gorgan (Iran) that were selected via multistage probability sampling. Data were collected using a 60-item questionnaire based on the Donabedian model with 5 dimensions (physical infrastructure, waiting room equipment, midwifery unit equipment, human resource infrastructure and access to services). Another questionnaire consisting of 14 questions was used to collect biographic information. Data were analyzed with SPSS (version 16). Normal distribution of variables was assessed using the Kolmogorov-Smirnov test. Parametric tests (binomial) and nonparametric coefficient were used for assessment of normal and non-normal data, respectively. All statistical analyses were performed at 95% confidence level (P <0.05). The Friedman test was used for one-way repeated measures analysis of variance by ranks. Results: The average total score of structure was 30.83 in the health centers. The average score for waiting room equipment, midwifery unit equipment, human resource infrastructure, physical infrastructure and access to services was 4.61, 13.94, 1.78, 6.56 and 3.94, respectively. Based on the average structure scores and prioritization, the rankings were as follows: physical infrastructure, midwifery unit equipment, waiting room equipment, access to services and human resource infrastructure. Conclusions: Generally, the low score of quality of services in the present study indicates the need for planning and paying proper attention to non-therapeutic aspects of health services and improvement of services quality.